Delayed traumatic purulent pericarditis with cardiac tamponade - A rare case report - Te-Kai Liao; Hiong-Ping Hii; Chao-Kun Chen; Li-Chin Cheng (Trauma Case Reports, 2022)
Thoracic trauma often results in immediate or delayed hemorrhage. There are few cases of purulent pericarditis with pericardial tamponade reported in the literature. If a devastating complication develops several weeks following blunt thoracic trauma, the causal relationship with the thoracic trauma event is less evident. As such, accurate diagnosis and subsequent effective treatment implementation is likely to be delayed. Herein, we present the case of a 46-year-old male patient with delayed purulent pericarditis that led to cardiac tamponade 2 weeks after the initial trauma.